APPLICATION OF THE COURSE REVIEW HORAY TYPE COOPERATIVE MODEL IN MATHEMATICS LEARNING IN CLASS IV SCHOOL ELEMENTARY TABA TINGGI - Pitri; Sukasno; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2020)
The results of interviews with teachers at School Elementary Taba Tinggi on February 2, 2020, obtained data that the average student learning outcomes in Mathematics were still below the KKM 65. From the results of daily student tests it was seen that there were still 13 students (46%) who scored below 65, and 15 students (54%) scored above the Standard 65. This can be identified from the way students solve the questions given by the teacher, they sometimes still lack the ability to apply the concepts and steps or material procedures to problem solving. This study aims to determine the completeness of the fourth grade mathematics learning outcomes of School Elementary Taba Tinggi after applying the Course Review Horay type cooperative model. The population in this study were students of class IV School Elementary Taba Tinggi with a total of 26 people consisting of one class, because of the small population so that the sample of this study were all members of the population, namely grade IV students of School Elementary Taba Tinggi with a total of 26 people. The research method used was pseudo-experiment. Data collection techniques in research using essay tests. Data analysis techniques with the steps: normality test and z test. The results of the post-test data analysis using the z test at a significant level = 0.05 and dk = 25 indicate a value> (2.56> 1.64). So it can be concluded that the learning outcomes of the fourth grade students of School Elementary Taba Tinggi after being applied with the Course Review Horay cooperative model are significantly complete.